Periodická tabulka prvků a její fyzikální interpretace - Zamkovská, Helena; Lacina, Aleš, 1947-; Masarykova univerzita. Ústav fyzikální elektroniky (2015)
Predložená bakalárska práca sa zaoberá podrobnou argumentáciou vývoja v porozumení Mendelejovej periodickej tabuľke prvkov od prvotných filozofií o štruktúre látok, cez úvahy chemického atomizmu až po jej kvantovomechanický popis v rámci jednoelektrónovej aproximácie.
The present work deals with the detailed reasoning in understanding the development of the Mendeleev periodic table of elements from primary philosophy of the structure of substances through chemical atomism consideration to the Quantum Mechanical description within the one-electron approximation.
Vedoucí práce: Aleš Lacina
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2015
Keywords: periodická soustava prvků; periodic system of elements; bakalářské práce; bachelor's theses